PROTOTYPE PENGUKUR DETAK JANTUNG, SATURASI OKSIGEN, DAN SUHU TUBUH MANUSIA SECARA PORTABLE - Septiar Rizkiansyah Sunarto; Alona Situmeang; Veronica Ernita Kristianti (Asosiasi Dosen Muda Indonesia, 2024)
In the world of health, there are many things that must be done to evaluate a person's health, including measuring heart rate, oxygen saturation and human body temperature. Measuring heart rate is very important because heart rate is a form of cardiovascular activity, while measuring oxygen saturation is the oxygen level which plays an important role in the metabolic processes of the human body and measuring body temperature as an important indicator of a person's health. The development of technology for measuring heart rate, oxygen saturation and body temperature is becoming increasingly important because it requires continuous or periodic monitoring of these three parameters which can help detect diseases or health conditions that require medical attention early. This measurement tool is designed to be portable so that it can be accessed anywhere independently by the user